PENGARUH AKTIVITAS SENYAWA FLAVONOID YANGTERDAPAT DALAM MADU TERHADAP RESEPTORH4R SEBAGAI ANTIINFLAMASI - Deden Indra Dinata (Universitas Bhakti Kencana, 2014)
Hesperetin, luteolin, kaempferol, isorhamnetin, and galangin are an active compounds contained in the honey. The fifth of these compounds in vivo has as anti-inflammatory activity. Docking simulation was done to visualize the interaction between the fifth ligand to the histamine H4 receptor compared with synthetic compounds that proved JNJ7777120 act as receptor selective H4R antagonist with anti-inflammatory properties. Docking simulation results showed that JNJ777120 is best histamine H4 receptor antagonist compound, but the compound of hesperetin, luteolin, kaempferol, isorhamnetin, and galangin also predicted potential as histamine H4 receptor antagonist. Toxicological properties focused on carcinogenicity and mutagenicity as an important concern in human health and drug design structure are directly related. The conclusion was JNJ7777120 compound H4R antagonist compound was rated as the best, but the compound hesperetin, luteolin, kaempferol, isorhamnetin , and galangin also predicted potential as histamine H4 receptor antagonist . JNJ7777120, galangin , hesperetin , kaempferol, luteolin and non- carcinogens and mutagens are carcinogens while predictable isorhamnetin.